A preliminary study: exploring teachers’ perspectives on the role of gathering information in supporting teachers’ digital learning agility - Abdullah, Kamilah; Md Khambari, Mas Nida; Mohd Rosli, Nur Dania; Su, Luan Wong; Zakaria, Noor Syamilah; Hamzah, Siti Raba’ah; Moses, Priscilla (Asia-Pacific Society for Computers in Education (APSCE), 2023)
Gathering information is essential to enhancing teachers' digital learning agility. By gathering data, teachers can stay abreast of the latest digital technologies and tools, acquire new skills, and improve their teaching practices. This preliminary study explores the role of gathering information in supporting teachers’ digital learning agility. The preliminary study employed a qualitative research approach, using semi-structured interviews to collect data from three teachers. The findings reveal that teachers gather information related to student learning and digital technologies to improve their teaching practices and support their students' digital learning. The study highlights the importance of information gathering in enhancing teachers' digital learning agility and provides insights for the development of policies and initiatives aimed at facilitating the improvement of teachers' digital learning agility.